2023
DOI: 10.14336/ad.2023.0320
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ Transcribed by IRF1 in CD4+ Effector Memory T Cells Promotes Senescence-Associated Pulmonary Fibrosis

Abstract: Physiologically aged lungs are prone to senescence-associated pulmonary diseases (SAPD). This study aimed to determine the mechanism and subtype of aged T cells affecting alveolar type II epithelial (AT2) cells, which promote the pathogenesis of senescence-associated pulmonary fibrosis (SAPF). Cell proportions, the relationship between SAPD and T cells, and the aging-and senescence-associated secretory phenotype (SASP) of T cells between young and aged mice were analyzed using lung single-cell transcriptomics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Different studies have demonstrated that specific CD4+ T-cell subsets are necessary to alleviate some interstitial lung damage or maintain IFN-γ production, avoiding senescence-associated pulmonary fibrosis. 30,31 The up-sPD-L2 profile observed in those post-COVID-ILD patients with lung structural and functional alterations could affect other cell subsets; reports indicated that high expression of PD-L2 is related to the presence of a macrophage subpopulation with anti-inflammatory and profibrotic functions called M2, which leads to the inhibition of T-cells, and in tumor models has been described that high expression of PD-L2 is associated with a poor prognosis. 32,33 Several studies suggest that M2 macrophages play a central role in the pathogenesis of fibrosis; for instance, M2 secretes connective tissue growth factors to mediate the proliferation and migration of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have demonstrated that specific CD4+ T-cell subsets are necessary to alleviate some interstitial lung damage or maintain IFN-γ production, avoiding senescence-associated pulmonary fibrosis. 30,31 The up-sPD-L2 profile observed in those post-COVID-ILD patients with lung structural and functional alterations could affect other cell subsets; reports indicated that high expression of PD-L2 is related to the presence of a macrophage subpopulation with anti-inflammatory and profibrotic functions called M2, which leads to the inhibition of T-cells, and in tumor models has been described that high expression of PD-L2 is associated with a poor prognosis. 32,33 Several studies suggest that M2 macrophages play a central role in the pathogenesis of fibrosis; for instance, M2 secretes connective tissue growth factors to mediate the proliferation and migration of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ T‐cells are one of the leading players in driving the adaptive immune response, primarily secreting cytokines to regulate or activate other cell subsets. Different studies have demonstrated that specific CD4+ T‐cell subsets are necessary to alleviate some interstitial lung damage or maintain IFN‐γ production, avoiding senescence‐associated pulmonary fibrosis 30,31 …”
Section: Discussionmentioning
confidence: 99%